2014
DOI: 10.4028/www.scientific.net/amm.592-594.859
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Slotted Horn for Ultrasonic Plastic Welding

Abstract: Ultrasonic horns are tuned components designed to vibrate in a longitudinal mode at ultrasonic frequencies. Reliable performance of such horns is normally associated with the amplitude of vibration, uniformity of vibration amplitude at the working surface and the avoidance of modal participation by non-tuned modes at the operating frequency. In order to maximise vibration amplitude uniformity, standard slotting configurations are included in the horn design. In this work the slot position in the horn is optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
3
7
0
Order By: Relevance
“…From harmonic analysis, maximum displacement amplitude obtained at the output face of block horn is 29.6 µm (Table 4). It is also observed that the uniformity of displacement amplitude is 100% at output face of horn which is in good indenture with previous studies Dipin Kumar et al [8]. Figures 13 and 14 show the von-Mises stress measured in the slotted block horn.…”
Section: Fig 7 Modal Analysis Of Horn With Vertical Slotsupporting
confidence: 86%
See 3 more Smart Citations
“…From harmonic analysis, maximum displacement amplitude obtained at the output face of block horn is 29.6 µm (Table 4). It is also observed that the uniformity of displacement amplitude is 100% at output face of horn which is in good indenture with previous studies Dipin Kumar et al [8]. Figures 13 and 14 show the von-Mises stress measured in the slotted block horn.…”
Section: Fig 7 Modal Analysis Of Horn With Vertical Slotsupporting
confidence: 86%
“…The vibrations are longitudinal and the output face slotted block horn is perfectly flat which is highly desirable for ultrasonic multiple insertion. This significance is well connected with the results detailed by Dipin Kumar et al [8]. So, all the profiles of the slotted block horns are valid for performing harmonic analysis.…”
Section: Fig 7 Modal Analysis Of Horn With Vertical Slotsupporting
confidence: 83%
See 2 more Smart Citations
“…The stresses in cylindrical, conical, Gaussian, exponential and catenoidal horn designs are very low, but the amplitude of vibration at the tool end is also extremely less as compared to the step design [6,10,13,20,31,32]. Slots and holes have been incorporated in some horn designs to increase the amplitude of vibration and reduce stresses [7,26,[33][34][35][36][37][38][39][40]. The lengths and diameters of the cylindrical portions, cross sectional shape (circular to rectangular) [41] and the location of mountings has also been varied to optimize and improve the performance of ultrasonic horn [42][43][44].…”
Section: Introductionmentioning
confidence: 99%